Necrotizing enterocolitis - Guillermo Bauzá López; Rafael Trinchet Soler; Natividad Lahaba Liquí; Leandro Salcedo Frómeta; Norma Carmenate González; Juan Daniel Rodríguez Alarcón (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2005)
Necrosantizing enterocolitis constitutes the most frequent and devastator gastrointestinal emergency in newborn patients, affecting especially premature patients and those with low weight (< 1500 g) during the two first weeks of life, that by some motive have suffered episodes of anoxy during the labor or shortly after and in which habitually the oral diet has been initiated. It can be seen in small infants, especially in the less than 3 months and associated to diarrhea. It is reported between 15 and 75 cases by each 1000 admissions in a unit of neonatal intensive cares. The mortality varies from 10 to 40%, greater in groups of high risk and is greater than the surgical mortality of all the congenital anomalies of the digestive tract combined. We presented the Good Clinical Practices Guideline for Necrotizing enterocolitis, approved by consensus in the 2nd National Good Clinical Practices Workshop in Pediatric Surgery (Manzanillo, Cuba, September 31 - October 3, 2002).